Locomotion control of Caenorhabditis elegans through confinement - Lebois, Félix; Sauvage, Pascal; Py, Charlotte; Cardoso, Olivier; Ladoux, Benoit; Hersen, Pascal; Di Meglio, Jean Marc (Biophysical Journal, 2012)
The model organism Caenorhabditis elegans shows two distinct locomotion patterns in laboratory situations: it swims in low viscosity liquids and it crawls on the surface of an agar gel. This provides a unique opportunity to discern the respective roles of mechanosensation (perception and proprioception) and mechanics in the regulation of locomotion and in the gait selection. Using an original device, we present what to our knowledge are new experiments where the confinement of a worm between a glass plate and a soft agar gel is controlled while recording the worm's motion. We observed that the worm continuously varied its locomotion characteristics from free swimming to slow crawling with increasing confinement so that it was not possible to discriminate between two distinct intrinsic gaits. This unicity of the gait is also proved by the fact that wild-type worms immediately adapted their motion when the imposed confinement was changed with time. We then studied locomotory deficient mutants that also exhibited one single gait and showed that the light touch response was needed for the undulation propagation and that the ciliated sensory neurons participated in the joint selection of motion period and undulation-wave velocity. Our results reveal that the control of maximum curvature, at a sensory or mechanical level, is a key ingredient of the locomotion regulation. © 2012 by the Biophysical Society.
CRIS-Team Scopus Importer:2024-02-19